2017
DOI: 10.1002/mame.201700027
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large Area Broadband and Omnidirectional Antireflective Transparent Foils by Roll‐to‐Roll Extrusion Coating

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 51 , 52 The nanoimprinting process based on roll-to-roll thermal nanoimprinting, or the roll-to-roll extrusion coating nanoimprinting and coating process, would also need to be optimized in order to achieve good replication fidelity of the designed nanopattern and uniformity of the coating. 53 , 54 Such processes have been demonstrated in industry for fabricating functional nanopatterns such as antireflection, superhydrophobic, and nanophotonic surfaces. 55 − 57 There are likely to be additional challenges with coatings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 51 , 52 The nanoimprinting process based on roll-to-roll thermal nanoimprinting, or the roll-to-roll extrusion coating nanoimprinting and coating process, would also need to be optimized in order to achieve good replication fidelity of the designed nanopattern and uniformity of the coating. 53 , 54 Such processes have been demonstrated in industry for fabricating functional nanopatterns such as antireflection, superhydrophobic, and nanophotonic surfaces. 55 − 57 There are likely to be additional challenges with coatings.…”
mentioning
confidence: 99%
“…It is worth noting that successful process integration would involve overcoming various technical challenges and would also require iterative optimization. For example, fabrication of the roll mold would require developing an AAO-based roller mold which could be fabricated by means of anodization or a nickel-based nanomold which could be fabricated using electron beam lithography and electroforming. , The nanoimprinting process based on roll-to-roll thermal nanoimprinting, or the roll-to-roll extrusion coating nanoimprinting and coating process, would also need to be optimized in order to achieve good replication fidelity of the designed nanopattern and uniformity of the coating. , Such processes have been demonstrated in industry for fabricating functional nanopatterns such as antireflection, superhydrophobic, and nanophotonic surfaces. There are likely to be additional challenges with coatings. The UASC process could be integrated into a production line by using multiple ultrasonic spraying nozzles.…”
mentioning
confidence: 99%
“…The presence of the sub-wavelength nanostructures enables a gradual change of the effective refractive index between the air and the moth-eye medium, leading to excellent AR properties known as the “moth-eye effect” [ 9 , 10 ]. Bioinspired moth-eye patterns have been successfully fabricated using micro- and nanofabrication methods and employed as AR coatings [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Replication of such nanostructures was carried out on several materials, including silicon [ 19 , 20 ], vanadium dioxide [ 21 ], chalcogenide glass [ 15 ], and transparent polymer foils [ 20 ], where measurements showed a reflectance of less than 0.5% for wavelengths between 500 to 900 nm, an absorption of 99% in the visible range, a transmittance above 70% for wavelengths between 3.3 to 13 µm, and above 90% in the visible range, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinspired moth-eye patterns have been successfully fabricated using micro- and nanofabrication methods and employed as AR coatings [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Replication of such nanostructures was carried out on several materials, including silicon [ 19 , 20 ], vanadium dioxide [ 21 ], chalcogenide glass [ 15 ], and transparent polymer foils [ 20 ], where measurements showed a reflectance of less than 0.5% for wavelengths between 500 to 900 nm, an absorption of 99% in the visible range, a transmittance above 70% for wavelengths between 3.3 to 13 µm, and above 90% in the visible range, respectively. Both hierarchical and nanostructures with AR properties rely mainly on the interaction of light with subwavelength structures, enabling a generally low reflectance over a large wavelength range.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that light out-coupling efficiency of OLEDs with stacked triple emission units was over 2 times of conventional one, resulting in drastic increase in external quantum efficiency and current efficiency. Murthy et al 29,30 investigated the fabrication and performance of broadband and omnidirectional antireective polymer foils, in the visible spectrum (400-800 nm), which were fabricated by a high throughput roll-to-roll extrusion coating process. Although the moth-eye nanostructure array has been partially applied in the solar cells, its application in Ag-mesh TCEs for transmittance improvement has not been reported and the effects on Ag-mesh layer aer the addition of the moth-eye nanostructure has not been investigated.…”
Section: Introductionmentioning
confidence: 99%